2015
DOI: 10.1111/dom.12439
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of canagliflozin on serum uric acid in patients with type 2 diabetes mellitus

Abstract: Hyperuricaemia is associated with an increased risk of gout, kidney stones and cardiovascular disease. The present post hoc analysis of pooled data from four placebo‐controlled phase III studies assessed the effect of canagliflozin, a sodium‐glucose co‐transporter 2 inhibitor, on serum uric acid levels in patients with type 2 diabetes mellitus (T2DM) and in a subset of patients with hyperuricaemia [defined as baseline serum uric acid ≥475 µmol/l (∼8 mg/dl)]. At week 26, canagliflozin 100 and 300 mg were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 13 publications
8
109
2
7
Order By: Relevance
“…Moreover, SGLT2 inhibitors reduce SUA levels, possibly due to mediating GLUT9 urate transporter via induction of glycosuria [10,89]. Recent clinical data showed that SGLT2 inhibitors, canagliflozin, dapagliflozin and empagliflozin, reduced SUA levels compared with placebo [8,9]. Ongoing trials may provide further insight into the effects of SGLT2 inhibitors on SUA and renal outcomes.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SGLT2 inhibitors reduce SUA levels, possibly due to mediating GLUT9 urate transporter via induction of glycosuria [10,89]. Recent clinical data showed that SGLT2 inhibitors, canagliflozin, dapagliflozin and empagliflozin, reduced SUA levels compared with placebo [8,9]. Ongoing trials may provide further insight into the effects of SGLT2 inhibitors on SUA and renal outcomes.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…The debate, however, continues regarding whether hyperuricemia plays a causal role in the progression of CKD or is simply a marker of renal dysfunction [7]. Of most recent, the unexpected finding that sodium glucose transporter 2 (SGLT2) inhibitors for type 2 diabetes mellitus (T2DM) modestly decrease serum uric acid (SUA) sheds light on the UA metabolism in the kidney [8][9][10]. In this review, we will describe the up-to-date knowledge on UA and its metabolism in the setting of CKD and demonstrate a line of evidence when and how to target SUA to inhibit the progression of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of serum uric acid levels has been seen with SGLTi-2 due to increased urinary excretion. 29,30 No increase in kidney uric acid stones was observed with SGLTi-2. 30 This new class of drugs has already been shown to reduce glycemic levels in animals and humans with type 1 DM (T1DM), in addition to allowing a reduction in insulin dosage.…”
Section: The Kidney As a Treatment Targetmentioning
confidence: 96%
“…29,30 No increase in kidney uric acid stones was observed with SGLTi-2. 30 This new class of drugs has already been shown to reduce glycemic levels in animals and humans with type 1 DM (T1DM), in addition to allowing a reduction in insulin dosage. [31][32][33] These drugs could, thus, be used as an adjuvant therapy in the treatment of DM1, with low risk of hypoglycemia and without weight gain.…”
Section: The Kidney As a Treatment Targetmentioning
confidence: 96%
“…Rasburicase found its application in acute urate nephropathy, as in tumor lysis syndrome. In more recent times, canagliflozin, a glycosuric agent inhibiting the glucose transporter SGLT1, was also found to have uricosuric effect [38]. Incidentally, the serendipitous finding that commonly used drugs exert uricosuric effect is not new, such as in the case of losartan [39], fenofibrate [40] and more recently sevelamer [41].…”
Section: Urate-lowering Therapy (Ult)mentioning
confidence: 99%